Utility of environmental DNA analysis for effective monitoring of invasive fish species in reservoirs. Issue 6 (23rd June 2021) - Jo, Toshiaki; Ikeda, Saki; Fukuoka, Arisa; Inagawa, Takashi; Okitsu, Jiro; Katano, Izumi; Doi, Hideyuki; Nakai, Katsuki; Ichiyanagi, Hidetaka; Minamoto, Toshifumi
Abstract: Dam‐mediated biological invasions are a serious problem all over the world. Once established in reservoirs, the invasive species have catastrophic impacts on the river ecosystems downstream, and thus, rapid monitoring of invasive species is an urgent issue for the effective removal of them and the conservation management of native ecosystems. Here, we verified the utility of environmental DNA (eDNA) analysis as a tool to effectively monitor three invasive fish species (bluegill, largemouth bass, and smallmouth bass) in reservoirs using multiplex real‐time PCR. First, to determine the optimal sampling location and season to detect eDNA from these species, we analyzed the eDNA in water samples from shore and offshore sites in three reservoirs all year around. We found that eDNA detection rates either did not differ between sampling locations or were higher for shore than offshore sites. In addition, eDNA detection rates were higher in spring (breeding season of target species) and/or summer than winter. Second, we extensively surveyed the distribution of the three species in 30 reservoirs in Japan using eDNA analysis. Consequently, a single eDNA‐based surveillance in summer allowed to match approximately 90% of the presence/absence of the invasive fish species known from 27 yr of administrative capture‐based surveillances. Given these results, we recommend collecting the replicated water samples from shore sites in summer or the breeding season for the effective detection of invasive fish eDNA in reservoirs. Our eDNA assays with multiplex real‐time PCR enable the rapid and sensitive monitoring of invasive fish distribution in reservoirs.